2014
DOI: 10.1007/s11357-014-9737-x
|View full text |Cite
|
Sign up to set email alerts
|

Old-onset caloric restriction effects on neuropeptide Y- and somatostatin-containing neurons and on cholinergic varicosities in the rat hippocampal formation

Abstract: Caloric restriction is able to delay age-related neurodegenerative diseases and cognitive impairment. In this study, we analyzed the effects of old-onset caloric restriction that started at 18 months of age, in the number of neuropeptide Y (NPY)-and somatostatin (SS)-containing neurons of the hippocampal formation. Knowing that these neuropeptidergic systems seem to be dependent of the cholinergic system, we also analyzed the number of cholinergic varicosities. Animals with 6 months of age (adult controls) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…These inhibitory neurons expressing PV and SOM, among the most affected populations impacted by aging in the hippocampus (26,27,31,59,60), have been shown to play important roles in learning and memory operations (28)(29)(30)(31)61). As our memory-guided learning task plausibly engages hippocampal processes, the positive changes recorded in inhibitory neuronal populations presumably reflect the fact that our simple form of training has induced physical and functional changes that have had positive, generalized impacts expressed very broadly across forebrain networks.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These inhibitory neurons expressing PV and SOM, among the most affected populations impacted by aging in the hippocampus (26,27,31,59,60), have been shown to play important roles in learning and memory operations (28)(29)(30)(31)61). As our memory-guided learning task plausibly engages hippocampal processes, the positive changes recorded in inhibitory neuronal populations presumably reflect the fact that our simple form of training has induced physical and functional changes that have had positive, generalized impacts expressed very broadly across forebrain networks.…”
Section: Discussionmentioning
confidence: 91%
“…The behavioral task applied in the current study required animals to identify a remembered target stimulus presented against a background of nontarget (distracting) stimuli. Inhibitory interneurons expressing PV and SOM in the hippocampus are among the most affected cell populations impacted by aging (26,27) and have long been argued to play critical roles in learning and memory (28)(29)(30)(31). Here we asked if our memory-based go/no-go training task applied in young adulthood detectably impacted the status of these key neuronal populations in the dentate gyrus (DG) and the CA1 subfield of the hippocampus.…”
Section: Resultsmentioning
confidence: 99%
“…Quintas et al reported that late-life CR increased SIRT1 in rat hippocampus (Quintas et al, 2012). Cardoso et al found that 18-mo old rats subjected to CR for 6 mo exhibited some protection against age-related decline in neuropeptide Y (NPY)-and somatostatin (SS)-containing neurons in the hippocampus (Cardoso et al, 2014). …”
Section: At What Age Does Cr No Longer Produce Benefits?mentioning
confidence: 99%
“…injection is better tolerated during long periods of time (2 months) and using high doses (300 mg/kg). 17,24 We focused the present study on the hippocampal formation (HF), a brain limbic region particularly affected by aging [25][26][27][28][29] and presenting the hallmarks of neuronal agerelated deterioration. 14,16 Furthermore, because d-galactose may interfere with neurogenesis, 9,30 we decided to analyze the effects of the high-dose d-galactose on the neurogenesis of the hippocampal dentate granule cells using two neurogenic markers, doublecortin (DCX) and Ki-67, that are easily quantified in young rodents.…”
Section: Introductionmentioning
confidence: 99%